Os mascarados das Folias de Reis: uma análise das máscaras da Companhia Santa Cecília, de São Caetano do Sul, no ABCD paulista, e da Companhia da Serraria, de São Thomé das Letras, no Sul de Minas Gerais (2009-2012) - Gorzoni, Priscila de Paula (2014)
The masks are essential accessories in the visual of men and women from different cultures and eras. They are used in religious and social rituals, parties and folkloric festivities. Its meaning is different, serve as mediators during religious rituals, as well as in leisure festivities. The word mask originates from the Latin mascus or masca = ghost , or in Arabic maskharah = clown , man in disguise . In festivals, among them the Kings Folly, the masks are the main accessories of marungos, bastions or clowns. They serve not only to incorporate the character reveler how to produce a catharsis among viewers. This paper will analyze the masks of two companies of Kings Folly: one is the Santa Cecília Company, in São Caetano do Sul (SP), and the other is the Company of the Sawmill, of São Thomé das Letras (MG). At work topics such as cooking, materials, rituals and character who wears the mask are treated